Pengaruh Keterampilan, Modal, dan Teknologi Terhadap Produktivitas Petani Padi di Kecamatan Selemadeg Timur Kabupaten Tabanan - Ni Putu Fina Cintya Dewi; Kadek Rai Suwena (Universitas Pendidikan Ganesha, 2026)
This study aims to examine the variables of skills, capital, and technology partially and simultaneously to determine whether they have an effect on the productivity of rice farmers in East Selemadeg District, Tabanan Regency. This study is quantitative causal in nature and uses a questionnaire as the data collection method. The sample consisted of 193 respondents. The sampling technique used was proportioned stratified random sampling. The analysis technique used is multiple linear regression analysis with partial hypothesis testing (t-test) and simultaneous hypothesis testing (F-test). The results of this study show that: (1) skills have a positive and significant effect on the productivity of rice farmers in Selemadeg Timur District, Tabanan Regency, (2) capital has a positive and significant effect on the productivity of rice farmers in Selemadeg Timur Subdistrict, Tabanan Regency, (3) technology has a positive and significant effect on the productivity of rice farmers in Selemadeg Timur Subdistrict, Tabanan Regency, (4) skills, capital, and technology have a simultaneous effect on the productivity of rice farmers in Selemadeg Timur Subdistrict, Tabanan Regency.